2018
DOI: 10.1371/journal.pone.0191992
|View full text |Cite
|
Sign up to set email alerts
|

Potential disruption of seed dispersal in the absence of a native Kauai thrush

Abstract: Hawaii has experienced a catastrophic decline in frugivorous native birds coupled with the introduction of non-native species. Puaiohi (Myadestes palmeri), a critically endangered thrush, is the sole extant native songbird capable of dispersing fleshy fruited plants in the rainforest of Kauai island, Hawaii. As this species has declined to occupy a small proportion of its original range, a suite of largely omnivorous non-native birds have been introduced to this region, including the common and widespread Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Recent studies of seed dispersal in Hawaii found non‐native birds frequently consume fruit with small seeds (Chimera & Drake, 2010; Culliney et al., 2012; Pejchar, 2015; Vizentin‐Bugoni et al., 2019) and in studies using seed rain traps, the maximum seed width of animal‐dispersed seeds was 2.23–8.1 mm, depending on the study (Appendix S3: Tables S1–S3; Chimera & Drake, 2010; Foster & Robinson, 2007; Hruska, 2019; Kaushik, Pejchar, & Crampton, 2018; Pejchar, 2015). While more work is needed to evaluate the roles of each disperser in the modern assemblage, from what is known, 8.1 mm in width appears to be the largest seed that is dispersed (into seed rain traps) by modern frugivores.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of seed dispersal in Hawaii found non‐native birds frequently consume fruit with small seeds (Chimera & Drake, 2010; Culliney et al., 2012; Pejchar, 2015; Vizentin‐Bugoni et al., 2019) and in studies using seed rain traps, the maximum seed width of animal‐dispersed seeds was 2.23–8.1 mm, depending on the study (Appendix S3: Tables S1–S3; Chimera & Drake, 2010; Foster & Robinson, 2007; Hruska, 2019; Kaushik, Pejchar, & Crampton, 2018; Pejchar, 2015). While more work is needed to evaluate the roles of each disperser in the modern assemblage, from what is known, 8.1 mm in width appears to be the largest seed that is dispersed (into seed rain traps) by modern frugivores.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the introduction of a new frugivore differing in size from the native/s one/s might involve a different spatial distribution of seed sizes, which in turn might have implications for the plants, both at the population and community level (Kaushik et al. ).…”
mentioning
confidence: 99%
“…In some cases, alien species act as beneficial partners of native species, and to some extent can be functionally adequate replacements of native counterparts (Kawakami et al 2009;Burns 2012;García et al 2014;Pejchar 2015). In fact, in some cases, these alien species may be the only available partners acting as "rescuers" of mutualistic interactions and the derived ecosystem functions (Foster and Robinson 2007;Muñoz-Gallego et al 2019), despite having an overall negative effect on the native community by, for instance, enhancing further invasions (e.g., Kawakami et al 2009;Pejchar 2015;Wotton and McAlpine 2015;MacFarlane et al 2016;Kaushik et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hawaii, for example, has more invasive land bird species (58 species) than native species, and the implications of removing these must be carefully considered, as some fulfil important ecological niches of extinct native species (Kaplan, 2007). However, invasive birds disperse both native and invasive plants in Hawaii and do not fulfil the complete ecological role of larger native frugivores (which are becoming increasingly rare) due to their smaller gape sizes Kaushik et al, 2018).…”
Section: The Future Of Citizen Science and Invasive Bird Researchmentioning
confidence: 99%